The hybridity of Indies culture in Indonesian novel translation into French - Ediani, Arwatrisi; Sajarwa (JOALL (Journal of Applied Linguistics and Literature), 2023)
Postcolonial novels incorporating hybrid culture elements into the story present new problems for translation. The hybrid elements that appear in the source text can be maintained or removed in the translation process, depending on the strategy adopted by the translator. This research focus on the hybrid elements of an Indonesian postcolonial novel and the strategy for maintaining and eliminating hybridity in its French translation. The data source in this research is the novel Bumi Manusia (1980) by Pramoedya Ananta Toer as the source text and its translation in French. Using a qualitative approach with a comparative method, the analysis results show that most of the efforts to maintain hybridity are carried out in translating social life terms and self-names because they are related to the frequency of occurrence, the complexity of meaning, and identity. However, on the whole, the translation is less hybrid as more dehybridization occurs. Moreover, hybridity in Bumi Manusia and its French translation, Le Monde des hommes, is manifested differently. Although the translation tends to create a homologous space of one culture, it still shows linguistic and cultural hybridity.